Evaluation of a brief art psychotherapy group for adults suffering from mild to moderate depression: Pilot pre, post and follow-up study. Issue 3 (3rd July 2017) - Zubala, Ania; MacIntyre, Donald J.; Karkou, Vicky
ABSTRACT: Current therapies do not offer universal solutions for the 'global burden' of depression. By focusing on non-verbal communication and creativity, arts therapies might present a relevant treatment option but their effectiveness remains unclear. A pilot study was undertaken to evaluate a brief art therapy group for adults suffering from depression. Adults experiencing mild to moderate depression took part in art therapy and completed questionnaires at three points in time. The intensity of depression, levels of anxiety and general wellbeing were measured. Semi-structured interviews focused on participants' expectations and experience of therapy. A decrease in depressive symptoms was observed immediately after the therapy and at the follow-up, and a trend for improvement of subjectively perceived wellbeing was recorded. Potential benefits of therapy recognised by participants included: acceptance of depression, readiness to express emotions, sense of self and awareness of others, readiness for meaningful relationships, sense of achievement, sense of balance and new insights, growth and meaning. The statistically significant results and participants' experience indicate that art therapy may offer a valuable treatment option for depression, and further research is recommended. Future studies should explore ways of addressing both the outcomes and the process of therapy through creative methodological designs.